IMPLEMENTASI MIND MAPPING DENGAN MODEL KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMA NEGERI 2 TOMPASO - Pasaribu, Putri A; Tumbel, Ferny M; Nanlohy, Fanny N. (SOSCIED, 2025)
The results of interviews conducted at SMA Negeri 2 Tompaso on students in class X where student learning outcomes are still relatively low, this is due to the lack of student attention when the teacher teaches, students are less actively involved in the learning process because they are less interested in the material taught and the low interaction and cooperation between students. The type of research used is Classroom Action Research. This classroom action research (PTK) aims to improve the learning outcomes of class X students with the implementation of Mind Mapping with a cooperative model of the Two Stay Two Stray type at SMA Negeri 2 Tompaso. The research procedure is carried out in a cyclical manner. Each cycle consists of planning activities, implementation of actions, observations, and reflection activities. The subject of the research is class X odd semester of the 2025/2026 school year with a total of 22 students. The results of this study show an increase in classical student learning outcomes in cycle I to cycle II. The percentage of completeness of student learning outcomes classically in the first cycle was 45% and in the second cycle it increased so that it reached 86 completeness classically. Based on the results of the study, it is concluded that the implementation of Mind Mapping with the Two Stay Two Stray type cooperative learning model on biodiversity materials can improve student learning outcomes